Optimization of Moulding Composition for Quality Improvement of Sand Casting - Said, R.M.; Kamal, M.R.M.; Miswan, N.H.; Ng, S.J. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Sand casting is a versatile and commonly used manufacturing process in the metal casting industry. This method can be used in almost all types of metal and the sand is recyclable. However, the defects in casting production such as blowholes, pinholes, shrinkage, and porosity cause imperfection in green sand moulding. The aim of this project is to optimise the composition of silica sand, bentonite, water, and coal dust in green sand to reduce the defects in the casting products using the 24-factorial experiment design method, which can produce a total of 16 runs for experiment to investigate the ratio of the four parameters. Then the experiment results of compression strength are collected and the composition effect of green sand was investigated. The results shows value of the adjusted R-square indicated that 86.92% of the total variability was explained by the model and the model predicted and actual fitted well with the experiment data. An analysis using the Design Expert software identified that bentonite and water are the main interaction effects in all of the experiments. The optimal settings for green sand composition are 95g silica sand, 24g bentonite, 8g water, and 8g coal dust. This composition has an effect of compression strength 35kN/m2.